Radical-mediated dehydrative preparation of cyclic imides using (NH4)(2)S2O8-DMSO: application to the synthesis of vernakalant - Garad, Dnyaneshwar N.; Tanpure, Subhash D.; Mhaske, Santosh B. (Beilstein Journal of Organic Chemistry, 2015)
Ammonium persulfate-dimethyl sulfoxide (APS-DMSO) has been developed as an efficient and new dehydrating reagent for a convenient one-pot process for the synthesis of miscellaneous cyclic imides in high yields starting from readily available primary amines and cyclic anhydrides. A plausible radical mechanism involving DMSO has been proposed. The application of this facile one-pot imide forming process has been demonstrated for a practical synthesis of vernakalant.
Keywords: APS-DMSO; imides; practical synthesis; radical-mediated; vernakalant

Radical beckmann rearrangement and its application in the formal total synthesis of antimalarial natural product isocryptolepine via C-H activation - Mahajan, Pankaj S.; Humne, Vivek T.; Tanpure, Subhash D.; Mhaske, Santosh B. (Organic Letters, 2016)
The Beckmann rearrangement of ketoximes, mediated by ammonium persulfate-dimethyl sulfoxide as a reagent, has been achieved under neutral conditions. Based on the radical trapping and O-18-labeling experiments, the transformation follows a mechanism involving a radical pathway. The scope and generality of the developed protocol has been demonstrated by 19 examples. The developed protocol and Pd-catalyzed intramolecular double C-H activation were used as key steps in the formal total synthesis of antimalarial natural product isocryptolepine.